Sistem Pendukung Keputusan Menggunakan Metode WASPAS dalam Pemilihan Calon Ketua Komite Sekolah - Ardiansah, Temi (Journal of Data Science and Information Systems, 2024)
The selection of candidates for school committee chairman is an important process in maintaining the smooth management of the school. The role of the committee chairman is vital in coordinating committee activities, communicating with school stakeholders, and making strategic decisions. Key problems in selecting school committee chairmen can include objectivity in the selection process, lack of transparency in selection criteria, lack of participation from all relevant parties, and the potential for subjective preferences or biases in selecting candidates for school committee chair. The research objective of using the decision support system with the WASPAS method in the selection of candidates for school committee chairman is to provide a structured and measurable framework in selecting the most suitable candidate for school committee chair, as well as to integrate various criteria relevant to the role and responsibilities of school committee chairs and provide more objective and measurable decisions based on careful data analysis. The WASPAS method will help in solving complex problems in the selection of candidates for school committee chairman by integrating various relevant criteria and providing objective values based on the weights set by users. The use of the WASPAS method can provide strong support in the decision-making process that has an impact on selecting candidates for school committee chairman who are optimal and in accordance with the needs and goals of the school.